2013
DOI: 10.1038/jes.2013.40
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field exposure assessment in Europe radiofrequency fields (10 MHz–6 GHz)

Abstract: Average levels of exposure to radiofrequency (RF) electromagnetic fields (EMFs) of the general public in Europe are difficult to summarize, as exposure levels have been reported differently in those studies in which they have been measured, and a large proportion of reported measurements were very low, sometimes falling below detection limits of the equipment used. The goal of this paper is to present an overview of the scientific literature on RF EMF exposure in Europe and to characterize exposure within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
70
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 47 publications
6
70
0
3
Order By: Relevance
“…These studies used a single exposimeter worn by human subjects to measure whole body RF-EMF exposure, but the exposimeters were not calibrated on body. In fact the use of a single exposimeter, may result in measurement uncertainties, particularly those related to the body shielding effects, residual calibration, and the frequency response of the measurement device (Bolte et al, 2011;Gajšek et al, 2015;Iskra et al, 2011;Mann, 2010;Neubauer et al, 2010). Iskra et al (2011) suggested that the use of two exposimeters placed on different locations on the body may minimize the measurement uncertainties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies used a single exposimeter worn by human subjects to measure whole body RF-EMF exposure, but the exposimeters were not calibrated on body. In fact the use of a single exposimeter, may result in measurement uncertainties, particularly those related to the body shielding effects, residual calibration, and the frequency response of the measurement device (Bolte et al, 2011;Gajšek et al, 2015;Iskra et al, 2011;Mann, 2010;Neubauer et al, 2010). Iskra et al (2011) suggested that the use of two exposimeters placed on different locations on the body may minimize the measurement uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating personal exposure levels from various far-field RF-EMF sources have been mainly conducted in European countries (Bolte & Eikelboom, 2012;Frei et al, 2009;Gajšek et al, 2015;Sagar et al, 2016;Urbinello et al, 2014b;2014c;Vermeeren et al, 2013). There is a paucity of similar comparable data from elsewhere, including Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainties can reach up to 25-30 dB (Bolte et al, 2011;Iskra et al, 2011;Neubauer et al, 2010) and include shielding effects of the human body, the multidirectional nature of the incident RF-EMFs, residual calibration, the frequency response of the exposimeter, and the inability to detect signals below the lower detection limits, etc. (Bolte et al, 2011;Gajšek et al, 2015;Iskra et al, 2011 ;Mann, 2010;Neubauer et al, 2010). Measurement uncertainties in personal exposimetry could be reduced by employing on-body calibrated exposimeters (Thielens et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Several European studies indicate that mobile phone base stations are a major source of whole body exposure to RF-EMF (Bolte and Eikelboom, 2012;Frei et al, 2009;Gajšek et al, 2015;Urbinello et al, 2014b;2014c;Vermeeren et al, 2013). More specifically, mobile phone base stations are a dominant exposure source to the whole body in urban outdoor environments and on public transport Urbinello et al, 2014aUrbinello et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…There are different methods of exposure assessment used for RF-EMF, mainly based on: 1) Spot or long-term measurements; 2) Personal exposimetry and 3) Characterization of exposure based on activities and sources [8]. Since personal exposure levels in everyday life depends from personal lifestyle including time spent in specific environment and individual behavior such as usage of wireless-enabled devices, for determination of personal exposure pattern the use of Personal Exposure Meters (PEMs) are recommended [9].…”
Section: Introductionmentioning
confidence: 99%